Effect of alloying elements on the stacking fault energies of dilute al-based alloys - Gao Q.; Zhang H.; Yang R.; Fan Z.; Liu Y.; Wang J.; Geng X.; Gao Y.; Shang S.; Du Y.; Liu Z. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A systematic study of the stacking fault energy (γSF) for the dilute Al-based alloys (Al23X, Al47X and Al71X, where X = Al, Ag, Be, Ca, Cd, Co, Cu, Cr, Fe, Ga, Ge, Hf, In, K, La, Li, Mn, Mg, Ni, Na, Pb, Sc, Sn, Sr, Si, Ti, V, Zn, and Zr) has been performed by means of first-principles calculations. Alias shear deformation is adopted in the present investigations. The presently calculated γSF for Al is in favorable accordance with experimental and other theoretical data. For the targeted elements, the calculations indicate that Na, Si, K, Ca, Sc, Ga, Ge, Sr, Zr, In, Sn, La, Hf, and Pb, in any concentration we considered, decrease the γSF of Al, while Ag, Be, Cd, Co, Cu, Cr, Fe, Li, Mn, Mg, Ni, Ti, V, and Zn increase the γSF of Al, when the concentration of alloying elements is 1.39 at. % in the system. With increasing concentration of alloying elements, Li, Mg, V, Ti, and Cd change from increasing the γSF of Al to decreasing it, based on present investigations. Among the alloying elements, which decrease the γSF of Al, La decreases the γSF most significantly. It is also found that the γSF of Al-X generally decreases with the increase of equilibrium volume. The results obtained in the present work provide an insight into the design of Al based alloys.